Social capital and bank accounting transparency - Jin, Justin; Kanagaretnam, Kiridaran; Lobo, Gerald J.; Michael Lee-Chin & Family Institute for Strategic Business Studies (My University, 2015)
Using a sample of public and private banks and a county-level index for social capital, we study how social capital relates to accounting transparency. In a region with high social capital, individuals have a greater propensity to honor an obligation and there is greater mutual trust within a much denser network that deters opportunistic/self-serving actions such as misrepresentation of accounting numbers and taking excessive risk for personal gain (Jha and Chen 2015). Consistent with expectations, our analysis indicates that social capital is positively associated with accounting transparency (proxied by accounting restatements and income-increasing earnings management) and this relationship is stronger for small, unaudited private banks. Additionally, we document that social capital is negatively associated with bank risk taking in the 2000-2006 pre-financial crisis period. We also find that banks in low social capital counties that are likely to engage in higher risk taking and have lower financial reporting transparency experienced more bank failures and bank trouble during the 2007-2009 financial crisis. Valuation Insight: Jin, Kanagaretnam, and Lobo examine the role of social capital in the valuation of banks. In regions with high social capital there is greater mutual trust which deters opportunistic actions. As a result there is greater accounting transparency which has a positive impact on market value. Banks in low social capital regions have lower reporting transparency and experienced more failures during the 2007-2009 financial crisis.
52 p. ; Includes bibliographical references (pp. 31-34). ; "November 10, 2015." Jin thanks the DeGroote School of Business for its financial support. Jin and Kanagaretnam thank the Social Sciences and Humanities Research Council of Canada (SSHRC) for its financial support.
Keywords: Accounting transparency; Social capital; Restatements; Earnings management; Financial crisis; Bank failure